The ISO-SWS survey of molecular hydrogen lines in active galaxies - Kunze, D; Rigopoulou, D; Genzel, R; Lutz, D (1999)
We present a survey of molecular hydrogen line emission in nearby starburst and Seyfert galaxies. Excitation temperatures and gas masses for loci-lying energy levels of Hz are derived from the observed pure rotational lines. The H-2 (0-0) S(1) line in Seyferts is emitted by a "warm" gas at temperature of 120-140 K. This component accounts for 0.2-20 per cent of the total gas content. In starbursts the temperature of the S(1) emitting gas is somewhat higher (up to 210 K) and contributes typically a few per cent to the total gas mass (up to 9 per cent in M82). The S(5) and S(7) lines trace a "hotter" gas component at temperatures of about 1100K (up to 1700K in IC342) both in Seyfert and starburst galaxies. The excitation of the molecular hydrogen in starbursts and some of the Seyfert galaxies is dominated by UV-fluorescence. However it cannot be excluded that a part of the "warm" H-2 gas is thermally excited. For some of the Seyferts indications for shock excitation are found.